2002
DOI: 10.1183/09031936.02.02042001
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of CC16, SP-A and SP-B reflect tobacco-smoke exposure in asymptomatic subjects

Abstract: Since the 16-kDa bronchiolar Clara cell protein (CC16) and the alveolar surfactant-associated proteins (SP)-A and -B leak into the circulation when parenchymal health is disturbed, the aim of this study was to determine whether their serum levels could serve as early peripheral markers of tobacco smoke-induced epithelial injury.Sixty-nine (51 yrs (32-54) median (25-75th percentile)) nonsmokers and 54 (42 yrs (31-53)) asymptomatic smokers were enrolled in the study.Serum levels of SP-A did not differ between su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
96
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 48 publications
16
96
1
1
Order By: Relevance
“…In our study we found increase levels of SP-D in patients with smoker COPD and non-smoker COPD this might be due to deleterious effects oxidants from tobacco smoke and oxidants originated from endogenous sources on lung tissue cause release of SP-D in blood stream. The increased level of SP-D in the blood stream depends on the extent of injury to the lung tissue and is directly related to pulmonary function [25][26][27]. In our study we obtain inverse correlation between SP-D with FEV1% predicted and FEV1/FVC % ratio in COPD patients.…”
Section: Discussionsupporting
confidence: 60%
“…In our study we found increase levels of SP-D in patients with smoker COPD and non-smoker COPD this might be due to deleterious effects oxidants from tobacco smoke and oxidants originated from endogenous sources on lung tissue cause release of SP-D in blood stream. The increased level of SP-D in the blood stream depends on the extent of injury to the lung tissue and is directly related to pulmonary function [25][26][27]. In our study we obtain inverse correlation between SP-D with FEV1% predicted and FEV1/FVC % ratio in COPD patients.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies indicate that circulating CC16 levels are decreased in lung injures caused by agents like tobacco or hexavalent chromium 20, 21. Chronic exposure to toxic agents causes a decline in the overall Clara cells located in terminal and respiratory bronchioles, leading to a relatively low production level of circulating CC16.…”
Section: Discussionmentioning
confidence: 98%
“…The variables to be included in the multivariable models (age, sex, and current exposure to SHS) were selected a priori based on the published literature. 12,26,37 Due to the relatively small sample size, more variables in the same multivariable models could not be included, but additional analysis replacing current exposure to SHS with other potential confounders (such as maternal asthma or BSS) did not change the results (data not shown). Urine levels of CC16 could be also affected by several other factors (e.g., post-renal excretion of CC16, diurnal variation, and physical activity).…”
Section: Discussionmentioning
confidence: 99%
“…The variables to be included in the multivariable models (infant's age, sex, and current exposure to SHS) were selected a priori based on published literature. 12,26,29,37 First-order interactions were tested for between urine levels of CC16 and each of the covariates mentioned above.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation